Clinical and histopathological aspects of the insect bite hypersensitivity in horses - Oliveira-Filho, Jose Paes [UNESP]; Fabris, Viciany Erique [UNESP]; Goncalves, Roberto Calderon [UNESP]; Amorim, Rogerio Martins [UNESP]; Chiacchio, Simone Biagio [UNESP]; Borges, Alexandre Secorun [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
In this study, the clinical and histopathological aspects of insect bite hypersensitivity (IBH) were assessed in horses. For this purpose, 12 horses with histopathologically confirmed cases of IBH of the skin were selected. The 12 animals were from 10 stud farms located in different municipalities of the state of São Paulo, Brazil. The main clinical findings included severe pruritus, alopecia and signs of irritability. The lesions were diffuse and predominantly dorsal, with the mane, tail and face most commonly affected. Histologically, perivascular lympho-histiocytic and eosinophilic dermatitis were also evident. Other findings included orthokeratotic hyperkeratosis, acanthosis and spongiosis. Thus, it was concluded that IBH could be diagnosed in horses through the combined use of clinical and epidemiological data and histopathological findings.
Keywords: Dermatopathology; allergic dermatitis; Culicoides; pruritus; horses